Perceived susceptibility and vaccine hesitancy among mothers in completing basic immunization: A qualitative study - Amita, Dzikra Fitria; Risdianti, Helza; Firstania, Aurellia; Zaharany, Tsania Ayu; Rajagukguk, Sartika; Khoirot, Risyda Ma'arifatul; Fajri, Dinda Nur; Gunawan, Annisa Pratiwi; Pitora, Tobi (School of Health Sciences Al-Ma'arif, 2026)
Background: Immunization is a highly effective public health intervention to reduce child morbidity and mortality. However, declining immunization coverage in several regions of Indonesia, including North Bengkulu Regency, reflects growing vaccine hesitancy. In Arga Makmur, concerns about post-immunization adverse events (KIPI) influence mothers’ decisions, indicating a shift in perceived susceptibility within the Health Belief Model. Objective: This study aimed to explore mothers’ perceived susceptibility related to childhood immunization and how these perceptions contribute to vaccine hesitancy in Arga Makmur, North Bengkulu. Methods: A descriptive qualitative study was conducted between October and November 2022 in the working area of the Argamakmur Community Health Center, North Bengkulu Regency, Indonesia. Nine mothers of children with incomplete immunization status were selected using purposive sampling. Data were collected through semi-structured in-depth interviews, audio-recorded, transcribed verbatim, and analyzed using Braun and Clarke’s six-phase thematic analysis. Results: Four major themes emerged from the analysis: (1) fear that injections could cause illness in children, (2) suspicion regarding the safety of vaccines and medications, (3) perceptions that children were physically weak or unfit to receive immunization, and (4) fatalistic beliefs reflected in surrender to divine destiny. Mothers tended to perceive the risks associated with vaccination as more immediate and threatening than the risks posed by vaccine-preventable infectious diseases. These perceptions were reinforced by misinformation, social narratives, and personal observations of post-immunization reactions. Conclusion: Vaccine hesitancy among mothers in Arga Makmur is strongly associated with a shift in perceived susceptibility—from concern about infectious diseases toward fear of vaccine-related risks. Addressing this imbalance requires effective risk communication, strengthening trust in healthcare providers, counteracting misinformation, and implementing culturally and religiously sensitive health promotion strategies to improve immunization acceptance.